2021
DOI: 10.3390/ijerph18168774
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Changes in Eating Habits and Eating Behaviors of Women First Diagnosed with Gestational Diabetes

Abstract: As gestational diabetes, which is increasing steadily around the world, can cause complications in the mother and fetus, it is essential to change eating habits and eating behavior to prevent this. According to the 2020 American Diabetes Association recommendations, the food plan should be designed for the adequate calorie intake to achieve glycemic goals and consequently promote maternal and fetal health. Thus, the following study has used the qualitative theme analysis method to assess what it means for 28 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…Surprisingly, even Australian-born women adhering to specific diets, such as vegetarian, found that the dietary advice for managing GDM was inadequate. Restricting the consumption of cultural foods and the fear of eating were also reported in other studies ( 18 , 23–25 ). Better education about food cultures and diets among health professionals can provide more tailored dietary information to women of all ethnicities.…”
Section: Discussionsupporting
confidence: 73%
“…Surprisingly, even Australian-born women adhering to specific diets, such as vegetarian, found that the dietary advice for managing GDM was inadequate. Restricting the consumption of cultural foods and the fear of eating were also reported in other studies ( 18 , 23–25 ). Better education about food cultures and diets among health professionals can provide more tailored dietary information to women of all ethnicities.…”
Section: Discussionsupporting
confidence: 73%
“…Assessing the Adherence to the SHPDGs According to the scale in Table 1, the total scores ranged from 0 to 24. Based on these scores, the participants were classified into three independent groups to describe their level of adherence to the SHPDGs: high adherence (0-7), moderate adherence (8)(9)(10)(11)(12)(13)(14)(15), and low adherence (16)(17)(18)(19)(20)(21)(22)(23)(24). Notably, SHPDGs have unspecified recommendations regarding junk food and physical activity.…”
Section: Exploration Of Eating Behaviors (Ebs)mentioning
confidence: 99%
“…Throughout every stage of life, specific nutritional requirements affect health and the risk of diseases [ 12 ]. Eating habits (EHs) are developed early in life [ 3 , 13 ] and have a crucial influence on food and drink preferences in adulthood, a period when the likelihood of chronic disease development is high [ 12 ]. One concern is that these habits tend to persist into adulthood, making them resistant to change until old age [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may need insulin if their blood glucose is not controlled by changing their lifestyle (American Diabetes Association, 2021a). The partners of the pregnant women are also suggested to change their lifestyles to help pregnant women with GDM manage their blood glucose (Kim et al, 2021).…”
Section: Introductionmentioning
confidence: 99%